Genomic Evidence for Direct Transmission of mecC-MRSA between a Horse and Its Veterinarian - Ervin Albert; Judit Sahin-Tóth; Andrea Horváth; Márton Papp; Imre Biksi; Orsolya Dobay (MDPI AG, 2023)
Methicillin-resistant Staphylococcus aureus bearing the mecC gene (mecC-MRSA) has been reported from animals and humans in recent years. This study describes the first mecC-MRSA isolates of human and equine origin in Hungary (two isolates from horses and one from a veterinarian, who treated one of the infected horses, but was asymptomatic). MRSA isolates were identified by cultivation and PCR detection of the species-specific spa gene and mecA/mecC methicillin resistance genes. The isolates were characterized by antibiotic susceptibility testing, MLST, spa, SCCmec typing, PFGE and whole genome sequencing (WGS). All three isolates belonged to the ST130-t843-SCCmec XI genotype, and carried the mecC and blaZ genes. Apart from beta-lactam drugs, they were sensitive to all tested antibiotics. The isolates of the infected horse and its veterinarian had the same PFGE pulsotype and showed only slight differences with WGS. Hence, this is the first description of direct transmission of a mecC-carrying MRSA between a horse and its veterinarian. The emergence of mecC in the country highlights the importance of the appropriate diagnostics in MRSA identification.